1D Model to Predict Ejector Performance at Critical and Sub-critical Operation in the Refrigeration System. (August 2015) - Shi, Chaoyin; Chen, Huiqiang; Chen, Weixiong; Zhang, Shuangping; Chong, Daotong; Yan, Junjie
Abstract: A new 1D model using the real gas property is proposed to predict ejector performance at critical and sub-critical operational modes, while most previous 1D models usually used the ideal gas property and only predicted ejector performance at critical mode operation. Constant pressure mixing is assumed to occur inside the constant area section of the ejector at critical and sub-critical mode operation, and the effectiveness of the model is verified against experimental data. The results show that the proposed model accurately predicts ejector performance over all ranges of operation. The 1D model is a useful tool for predicting ejector performance within larger refrigeration cycle models.